Severe Diltiazem Poisoning Treated with Hyperinsulinaemia-Euglycaemia and Lipid Emulsion - Nadine Monteiro; Joana Silvestre; João Gonçalves-Pereira; Camila Tapadinhas; Vitor Mendes; Pedro Póvoa (Case Reports in Critical Care)
Introduction. Calcium channel blockers (CCBs) drugs are widely used in the treatment of cardiovascular diseases. CCB poisoning is associated with significant cardiovascular toxicity and is potentially fatal. Currently, there is no specific antidote and the treatment of CCB poisoning is supportive; however, this supportive therapy is often insufficient. We present a clinical case of severe diltiazem poisoning and the therapeutic approaches that were used. Case Report. A 55-year-old male was admitted to the intensive care unit (ICU) after voluntary multiple drug intake, including extended release diltiazem (7200 mg). The patient developed symptoms of refractory shock to conventional therapy and required mechanical ventilation, a temporary pacemaker, and renal replacement therapy. Approximately 17 hours after drug intake, hyperinsulinaemia-euglycaemia with lipid emulsion therapy was initiated, followed by progressive haemodynamic recovery within approximately 30 minutes. The toxicological serum analysis 12 h after drug ingestion revealed a diltiazem serum level of 4778 ng/mL (therapeutic level: 40–200 ng/mL). Conclusions. This case report supports the therapeutic efficacy of hyperinsulinaemia-euglycaemia and lipid emulsion in the treatment of severe diltiazem poisoning.